Research, processing and analysis of exploitation reliability results of high-speed radial diesel engine - Mihanović, Luka (Array, 2021)
This paper presents the research on reliability of high-speed radial marine diesel engine Zvijezda M 504 B2 based on experimental data of malfunctions on the engine and time required for repair. Exploitation reliability and failure intensity were calculated from operational data collected from the engine log book. Results were tested by computer program to determine the relevance of the obtained results. Mathematically calculated reliability model of high-speed radial marine diesel engine Zvijezda M 504 B2 showed continuous increasing function of the intensity of failure and the fact that the reliability of the engine can be reliably approximated by Weibull distribution. Based on the obtained results it has been shown that this distribution, regardless of its complexity, should be used in practice when calculating reliability of engines with similar constant and growing malfunction"s intensity. The conclusion is that proposed distribution enables a better depiction of the observed technical system and the impact of aging of components on the system reliability.